Evaluasi Kepuasan Pelanggan terhadap Kendaraan Motor Vario Menggunakan Metode Simple Additive Weighting (SAW) - Purnasiwi, Rona Guines; Tundo, Tundo (Computer Journal, 2025)
This study aims to measure the satisfaction level of Honda Vario motorcycle owners by applying the Simple Additive Weighting (SAW) method. SAW was chosen to evaluate various factors, including price, engine performance, fuel efficiency, safety, and riding comfort. A survey was conducted involving 100 Honda Vario owners to gain insights into their experiences. The results indicate that 18 participants were very satisfied, 39 satisfied, 30 moderately satisfied, and 13 dissatisfied. Comfort and fuel efficiency received the highest appreciation among users. Although some respondents mentioned shortcomings in certain features, most still prefer Honda Vario for daily transportation. These findings can assist manufacturers in understanding customer expectations and considering improvements in product quality as well as after-sales service. For prospective buyers, the results offer useful information to help match their choices with personal needs. By using the SAW approach, the evaluation process becomes more objective, supporting better decisions for both users and manufacturers.